The Great Gatsby [videorecording (DVD)] - Clayton, Jack, 1921-1995; Redford, Robert; Farrow, Mia, 1945-; Dern, Bruce; Black, Karen, 1939-2013; Wilson, Scott, 1942-2018-; Waterston, Sam; Chiles, Lois, 1947-; Da Silva, Howard, 1909-1986; Fitzgerald, F. Scott (Francis Scott), 1896-1940 (Paramount Home Video, 2003)
In 1920s Long Island, a mysterious American millionaire's efforts to recapture the sweetheart of his youth result in tragedy.